Molecular aspects of milk lipid synthesis and secretion in mammary epithelial cells - Chrissy Lalonde; Jana Kraft; Feng-Qi Zhao (Animal Nutriomics)
Milk fat is a high-value component of the U.S. dairy market. It is the major energy component of milk and is responsible for many organoleptic and technological characteristics of milk and dairy products. In addition, milk fat is unquestionably distinctive among all dietary fats that humans consume, as it is not only comprised of several hundred different fatty acids (FAs) but also contains a wide and unique array of bioactive lipids. Milk fat is dispersed in milk primarily in the form of fat globules. These cytoplasmic lipid droplets originate from mammary epithelial cells (MECs) and are secreted into the alveolar lumen surrounded by a membrane. Many advances in our knowledge of specific enzymes involved in milk lipid synthesis, the selectivity of the triacylglyceride (TAG) synthesis enzymes for specific FAs, the molecular mechanisms behind the uptake of long-chain FAs into the cells and the milk lipid secretion process have led to an improved understanding of the biology of milk fat synthesis. However, research to provide deeper insights into the mechanism of lipid synthesis in MECs is warranted and might lead to novel strategies to alter milk fat content and quality to benefit the dairy industry and meet dietary recommendations and consumer demands for foods that positively impact health. In this review, we aimed to provide a general overview of our current knowledge of the molecular aspects of milk lipid synthesis in MECs, from the uptake of blood-derived precursors to the intracellular formation of TAG-rich fat droplets secreted into milk as milk fat globules. We also highlight some current gaps in the knowledge that warrant further exploration. Given the importance of dairy food in the human diet, a better understanding of these processes could help develop novel strategies to alter milk fat composition in ways that benefit both human health and dairy producers.